Suppression of TNF-αand IL-1 Signaling Identifies a Mechanism of Homeostatic Regulation of Macrophages by IL-27 - Kalliolias, George D. (2010)
IL-27 is a pleiotropic cytokine with both activating and inhibitory functions on innate and acquired immunity. IL-27 is expressed at sites of inflammation in cytokine-driven autoimmune/inflammatory diseases, such as rheumatoid arthritis, psoriasis, inflammatory bowel disease, and sarcoidosis. However, its role in modulating disease pathogenesis is still unknown. In this study, we found that IL-27 production is induced by TNF-α in human macrophages (Mϕ) and investigated the effects of IL-27 on the responses of primary human Mϕ to the endogenous inflammatory cytokines TNF-a and IL-1. In striking contrast to IL-27–mediated augmentation of TLR-induced cytokine production, we found that IL-27 suppressed Mϕ responses to TNF-α and IL-1β, thus identifying an anti-inflammatory function of IL-27. IL-27 blocked the proximal steps of TNF-α signaling by downregulating cell-surface expression of the signaling receptors p55 and p75. The mechanism of inhibition of IL-1 signaling was downregulation of the ligand-binding IL-1RI concomitant with increased expression of the receptor antagonist IL-1Ra and the decoy receptor IL-1RII. These findings provide a mechanism for suppressive effects of IL-27 on innate immune cells and suggest that IL-27 regulates inflammation by limiting activation of Mf by inflammatory cytokines while preserving initial steps in host defense by augmenting responses to microbial products.